2011
DOI: 10.1111/j.1601-0825.2011.01840.x
|View full text |Cite
|
Sign up to set email alerts
|

Urban legends: recurrent aphthous stomatitis

Abstract: Recurrent aphthous stomatitis (RAS) is the most common idiopathic intraoral ulcerative disease in the USA. Aphthae typically occur in apparently healthy individuals, although an association with certain systemic diseases has been reported. Despite the unclear etiopathogenesis, new drug trials are continuously conducted in an attempt to reduce pain and dysfunction. We investigated four controversial topics: (1) Is complex aphthosis a mild form of Behçet’s disease (BD)? (2) Is periodic fever, aphthous stomatitis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
109
0
7

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(120 citation statements)
references
References 135 publications
4
109
0
7
Order By: Relevance
“…Aphthous ulceration is common but generally poorly responsive to antibiotics and antipyretics, and the range of agents trialled is testimony to their low efficacy. 1 Some ulceration that clinically mimics aphthae is serious and the differential diagnosis in a patient with oral ulceration and systemic lesions, such as genital ulceration, accompanied by fever, skin rashes and arthritis includes the possibility of aphthous-like ulceration 2 such as seen in Behcet syndrome 3 or other auto-inflammatory diseases. 2 These are disorders of innate immunity characterised by an exaggerated inflammatory response in the absence of autoantibodies or any identifiable infection which manifest as recurring ulcers but closer scrutiny will reveal episodes of fever and systemic inflammation affecting other mucosae, skin and joints -and with raised inflammatory markers such as the erythrocyte sedimentation rate.…”
Section: A New Therapeutic Agentmentioning
confidence: 99%
“…Aphthous ulceration is common but generally poorly responsive to antibiotics and antipyretics, and the range of agents trialled is testimony to their low efficacy. 1 Some ulceration that clinically mimics aphthae is serious and the differential diagnosis in a patient with oral ulceration and systemic lesions, such as genital ulceration, accompanied by fever, skin rashes and arthritis includes the possibility of aphthous-like ulceration 2 such as seen in Behcet syndrome 3 or other auto-inflammatory diseases. 2 These are disorders of innate immunity characterised by an exaggerated inflammatory response in the absence of autoantibodies or any identifiable infection which manifest as recurring ulcers but closer scrutiny will reveal episodes of fever and systemic inflammation affecting other mucosae, skin and joints -and with raised inflammatory markers such as the erythrocyte sedimentation rate.…”
Section: A New Therapeutic Agentmentioning
confidence: 99%
“…RAU in association with CD is predominantly of the minor variant with the average ulcer size being 5 mm with a non-keratinised mucosal distribution 5 . Clinically indistinguishable ulceration can be associated with conditions other than CD such as immunodeficiency states and Crohn's disease.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…While the exact cause of RAU in CD remains unknown; it may be potentially related to nutrient deficiencies associated with low serum iron, folic acid and vitamin B12. 5,12,29 RAU often regresses with the implementation of a GFD 29 .…”
Section: Clinical Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many therapeutic agents that have been used in treatment of RAS aiming to reduce the frequency of ulceration and to minimize the discomfort that associated with disease activity but the doctors and patients aims are to have full recovery and even cure, these agents include: chlorhexidine [4]; topical honey [25]; 5% lactic acid mouth wash [26]; Nigella sativa oil [27]; tetracyclin and their derivative (doxycycline and minocycline) [28]; BCG vaccine [29]; oral dapson and zinc sulfate [30]; oral steroid [31]- [34]; oral colchicine [35]; and oral clofazimine [31]. Recently, an Iraq study showed that oral isotretinoin had an effective therapeutic and prophylactic role in management of RAS [36].…”
Section: Introductionmentioning
confidence: 99%